Pengabdian Masyarakat Melalui Revitalisasi Lingkungan dan Pemberdayaan Komunitas dengan Pembuatan Taman, Pohon Natal dan Kegiatan Sosial Edukasi - Dongoran J; Tarigan H; Sinurat T; Manurung T; Sinuraya E; Sitanggang H; Situmorang D; Saragih S; Simarmata D (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Community Service (KKN) is a form of intracurricular which is an implementation of the Tridharma of Higher Education providing work and learning experiences for students in community empowerment. This KKN activity is an opportunity for creativity for students to think more critically in helping to advance the village through the potential and natural resources available in the village. Community service activities in the form of KKN are carried out for more than 1 month, starting from November 4 to December 7, 2024, located in Pealinta Dolok Saribu Village. The target of this community service activity is the general public of Pagaran Dolok Saribu village, elementary school children. The service is carried out in several stages, including observation, practice and discussion with village officials. After students conduct a survey of the location around the village, the Community Service Students determine the work program activities, namely 1. Revitalization of the Small Park Environment located in the PKK park, 2. Making Christmas Trees made from used bottle waste. 3. Social Education Activities, free tutoring carried out in the KKN Student post 4. Posyandu activities and elderly gymnastics in Pealinta Dolok Saribu village. Through KKN Activities in Pealinta Dolok Saribu Village, students can provide knowledge, time and energy that they have learned during their time on campus through various work programs that aim to help and provide benefits to the village.